The Main Views That Caused The Errors Of The Salafis (Eurasian Journal of Learning and Academic Teaching, 2026)
This article examines the core tenets of the Salafi movement within Islamic thought, focusing on its approach to sources of knowledge, its stance on the Sunnah, and its principle of adhering to the early generations. The study aims to thoroughly elucidate Salafi methods of understanding religion through an analysis of the views of prominent Salafi scholars such as Ibn Taymiyyah and Ibn Qayyim al-Jawziyyah. The methodology employed involves textual analysis and comparative study, highlighting the differences between the harmony of reason and revelation in Maturidi theology and the absolute prioritization of revelation in Salafism. The findings indicate that Salafis strictly adhere to the literal meanings of religious texts and largely reject taʼwil (allegorical interpretation), considering reason a supportive tool subservient to revelation. The article reveals Salafism's objective to avoid innovations and adhere to the religion in its pristine form.